2022
DOI: 10.1186/s12888-021-03411-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antipsychotic use in non-psychotic depressed patients: results from a clinical multicenter survey

Abstract: Background The combination of antipsychotics is not well studied among non-psychotic major depressive disorder (MDD). This study aims to explore the antipsychotics use in this population and its associated factors. Methods This cross-sectional and multi-site study was conducted in 11 sites of China. one Thousand five hundred three eligible MDD patients after 8–12 weeks of antidepressant treatment were included consecutively. A structured questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Comorbidities had some effect on augmentation risk, as reported also by Zhou et al 17 In our study, personality and anxiety disorders and substance abuse slightly increased the risk. It is interesting, that anxiety disorder increased the risk only in persons with moderate depression but not in severe depression.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Comorbidities had some effect on augmentation risk, as reported also by Zhou et al 17 In our study, personality and anxiety disorders and substance abuse slightly increased the risk. It is interesting, that anxiety disorder increased the risk only in persons with moderate depression but not in severe depression.…”
Section: Discussionsupporting
confidence: 87%
“…Among persons suffering from severe depression, 14.0% initiated antipsychotic augmentation. Zhou et al 17 have recently reported slightly higher results, as in their study AP augmentation was initiated to 179 of 834 (21.5%) young adults (18–44 years) with major depressive disorder.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations